Delayed Presentation of Post-Traumatic Porencephalic Cyst with CSF Rhinorrhoea - Ghimire, Anupam; Shrestha, Gentle Sunder (Nepalese Medical Journal, 2019)
Porencephalic cyst is a fluid filled intracranial lesion, which is usually congenital, but may develop following trauma. CSF rhinorrhoea occurs mostly following trauma and some can present years later, with resulting morbidity and the need for further management . We report an unusual case of post traumatic CSF rhinorrhoea four years after history of trauma. Initial CT scan following trauma was normal and was managed conservatively. Subsequently, patient presented with CSF rhinorrhoea after four years. CT scan showed porencephalic cyst of frontal lobe. CSF leak was managed conservatively and was advised for further neurosurgical intervention. Late onset CSF leak seems to be rare, but important complication of traumatic brain injury.